2021
DOI: 10.1021/acs.iecr.0c05118
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Water Imbibing into Oil-Saturated Nanoporous Media: Coupling Molecular Interactions, the Dynamic Contact Angle, and the Entrance Effect

Abstract: Spontaneous imbibition of hydraulic fracturing fluids into the water-wet inorganic media is a ubiquitous phenomenon, which has an important influence on tight/shale oil recovery and groundwater contamination. However, in nanoscale space, the fluid–solid (water–wall and oil-wall) molecular interactions, which can result in the nanoscale effects of the slip boundary and the varying interfacial fluid viscosity, will make the fluid flow behaviors be more complex and difficult to characterize. In this work, a new g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
(139 reference statements)
0
10
0
Order By: Relevance
“…Recent theoretical and experimental studies demonstrated that the contact angle changes with the flow velocity of the interface between moving phases. According to the molecular kinetic theory, , the dynamic contact angle can be described as a function of the equilibrium contact angle, flow velocity of the interface, and capillary number by cos nobreak0em.25em⁡ θ = cos nobreak0em.25em⁡ θ e α C a where θ e is the equilibrium contact angle, °; θ is the DCA, °; and α is an empirical parameter described by α = μ n o V o h .25em exp [ σ o w false( 1 + cos nobreak0em.25em⁡ θ false) λ w 2 k B T ] . A static contact angle (SCA) can be reached for α = 0; Ca is the capillary number characterizing the capillary forces and the viscous forces, C a = v μ σ .…”
Section: Mathematical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent theoretical and experimental studies demonstrated that the contact angle changes with the flow velocity of the interface between moving phases. According to the molecular kinetic theory, , the dynamic contact angle can be described as a function of the equilibrium contact angle, flow velocity of the interface, and capillary number by cos nobreak0em.25em⁡ θ = cos nobreak0em.25em⁡ θ e α C a where θ e is the equilibrium contact angle, °; θ is the DCA, °; and α is an empirical parameter described by α = μ n o V o h .25em exp [ σ o w false( 1 + cos nobreak0em.25em⁡ θ false) λ w 2 k B T ] . A static contact angle (SCA) can be reached for α = 0; Ca is the capillary number characterizing the capillary forces and the viscous forces, C a = v μ σ .…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…In this study, we numerically solve the dynamic imbibition model by the following procedures: Step-1: Input the parameters of the core sample and fluid properties; Step-2: Determine D f , τ, r max , and r e using the parameters of core samples; Step-3: Determine α using the values reported in the literature. , In this study, we set α = 11.6 for the DI model with the DCA, and set α = 0 for the DI model which considers a static contact angle (SCA); Step-4: Calculate the maximum time ( t max ) required for DI in a single capillary where r = r min ; Step-5: Calculate the imbibition volume at each time interval using eq . We discrete time and distance to calculate the imbibition volume using eq as follows: (a) Select a time interval Δ t and distance interval Δ r .…”
Section: Mathematical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because many factors influence the slip length, it is not easy to analyze these factors. Wang et al considered that the influence of wettability is most significant at the low shear rate, as shown in Figure , and expressed as follows …”
Section: Mathematical Model Of Si and Fi In A Single Capillarymentioning
confidence: 99%
“…In 2019, Wang [110] put forward the model of apparent viscosity and enhancement factor, which is related to the contact angle, pore size and shapes, and the boundary slip velocity. In 2021, he [111] also established a new generalized imbibition model in inorganic nanopores and porous media by LBM. He thinks that the proposed model can accurately t = 0 t = 40000 t = 80000 t = 160000 t = 320000 t = 740000 10 Geofluids describe the mechanism of the oil-water interface and is applicable to different nanoscale effects.…”
Section: Modeling Techniques For Imbibitionmentioning
confidence: 99%